Anterior mediastinal tracheostomy for malignancy: analysis of 12 cases. (April 2013) - Bagheri, Reza; Rahim, Mohammad Bagher; Majidi, Mohammadreza; Tabari, Azin; Akhlaghi, Saeed; Tabari, Azadeh
Introduction: Anterior mediastinal tracheostomy is indicated in extensive cervicothoracic malignancy with cervical mediastinal involvement of the trachea. This study was designed to assess the therapeutic outcome of anterior mediastinal tracheostomy. Methods: From 2001 to 2010, 10 men and 2 women, with a median age of 64.5 years, underwent anterior mediastinal tracheostomy and were followed up for at least for 1 year. Seven patients had stomal recurrence following laryngectomy, 3 had carcinoma of the cervical esophagus, 1 had squamous cell carcinoma of the trachea invading the subglottic larynx, and 1 had adenoid cystic carcinoma of the trachea invading the subglottic larynx. They were evaluated in terms of etiology of the primary lesion, previous treatment, complications, hospital death, and Kaplan-Meier survival estimate. Results: The tumor was completely resected in all cases. Postoperative complications included atelectasis (3 patients), stomal necrosis (1 patient), and anastomotic leak (1 patient). There were 2 (16.6%) postoperative hospital deaths. The mean duration of follow-up was 23 months, and the mean overall survival time was 25.59 months. Survival was calculated for 3 groups based on primary etiology: stomal recurrence of laryngeal carcinoma (12.85 months), cervical esophageal cancer (28 months), and primary malignancy of the trachea (29 months). Conclusion: Because of the small number of patients, a definitive conclusion was difficult, but acceptable morbidity, mortality, and relative survival in selected patients, in whom an extensive cervicothoracic operation was performed by an experienced and skilled team of surgeons, demonstrated that anterior mediastinal tracheostomy can be a helpful procedure for patient survival.